Pre-admission therapy for childhood acute diarrhoea - a hospital-based study - Ng, Y.J.; Lo, Y.L.; Lee, W.S. (2009)
Acute gastroenteritis (AGE) is a common illness among infants and children contributing to significant mortality and morbidity. As such, appropriate treatment received prior to hospital admission is of utmost importance. This retrospective observational study aimed to determine preadmission management in paediatric patients prior to hospital admission. Two hundred and twenty-two case notes of paediatric AGE patients were reviewed over a 12-month period. One hundred and fifty-four patients received medications prior to admission with 143 (92.9) patients received known classes of medications. Antipyretic agents were the most commonly prescribed (69.2), followed by antibiotics (38.5), anti-emetics (35.7), oral rehydration salts (29.4) and antidiarrhoeals (28.0). The mean duration of stay in hospital was slightly shorter in patients, who received prior medications than those who did not (2.22 vs. 2.32 days respectively). Seventy per cent of children admitted for AGE were treated suboptimally prior to hospital admission with oral rehydration salts being largely under-utilized, despite their proven efficacy and safety. Sex, race and age had no influence on the type of preadmission treatment. A greater effort should be made to educate the general public in the appropriate treatment of AGE.